Screening of probiotic strains from human breast milk and evaluation of their potential anti-obesity properties - Xiangxiang Zhao; Ke Xie; Yanghong Wang; Yao He; Hua Wei; Xueying Tao (Journal of Functional Foods, 2025)
Human breast milk is a recognized potential source of probiotics. In this study, sixteen lactic acid bacteria (LAB) were isolated from human breast milk. Among them, eleven strains, including seven strains of Limosilactobacillus fermentum (L. fermentum) and four strains of Lacticaseibacillus paracasei (L. paracasei), were systematically evaluated for their probiotic properties. Comprehensive assays, including survival in acidic and simulated intestinal fluid, antioxidant capacity, surface physicochemical properties, adherence to intestinal epithelial cells, antimicrobial properties, and in vitro anti-obesity potential (α-glucosidase inhibitory activity, cholesterol removal capacity, bile salt hydrolase activity (BSH) and lipase activity), as well as antibiotic resistance patterns and a principal component analysis, were conducted. The results showed that ELPA01 could effectively reduce cholesterol levels and inhibit Gram-negative pathogens, while ELFE07 exhibited strong α-glucosidase inhibitory activity and high BSH and antioxidant activities. These results demonstrate that both ELPA01 and ELFE07 may be promising candidates for the next generation of anti-obesity probiotics.